The Influence of the Inquiry Learning Model on Critical Thinking Ability in Madrasah Students - Goddess Wijaya, Dinda Intan Azzahra; Fairuz, Larisa Shafa; Purnomo, Halim (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to analyze and synthesize various results of previous research regarding the influence of the inquiry learning model on students' critical thinking abilities, especially in madrasas, through a systematic literature review (SLR) approach. This study identified various factors that influence the effectiveness of the inquiry learning model such as the role of the facilitator, learning structure, and student characteristics. by systematically reviewing scientific articles published in the last 10 years from accredited journals using a selection process with predetermined inclusion and exclusion criteria. The research results show that the implementation of inquiry learning has a positive and significant influence on improving students' critical thinking skills through an approach that encourages students' exploration, analysis and reflection. Apart from that, this model has also been proven to be effective in various levels of education and subjects. In conclusion, inquiry learning is a relevant strategy and has the potential to be further developed to support strengthening students' critical thinking skills.